2018
DOI: 10.1097/md.0000000000010277
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital mortality and morbidity of pediatric scoliosis surgery in Japan

Abstract: Several previous reports have elucidated the mortality and incidence of complications after pediatric scoliosis surgery using nationwide databases. However, all of these studies were conducted in North America. Hence, this study aimed to identify the incidence and risk factors for in-hospital mortality and morbidity in pediatric scoliosis surgery, utilizing the Diagnosis Procedure Combination database, a national inpatient database in Japan.We retrospectively extracted data for patients aged less than 19 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Previously it's been observed that increase in serum creatinine was significantly high in patients with long duration of bypass as compared to short duration and ARF was also higher in long duration of surgery as compared to short duration. But the inhospital mortality was almost equal in both groups 7 . Renal complications were also significantly associated with CPB >90 min 8,9 .…”
Section: Introductionmentioning
confidence: 85%
“…Previously it's been observed that increase in serum creatinine was significantly high in patients with long duration of bypass as compared to short duration and ARF was also higher in long duration of surgery as compared to short duration. But the inhospital mortality was almost equal in both groups 7 . Renal complications were also significantly associated with CPB >90 min 8,9 .…”
Section: Introductionmentioning
confidence: 85%
“…There have been several studies that investigated the incidence or risk factors for complications following surgery for pediatric deformity; however, there have been a very few studies that described UPROR. [1][2][3][4][5][6][7][8] Because UPROR is a useful indicator for both estimating an economic burden of postoperative complications and measuring surgical quality, it is quite reasonable to focus on UPROR. [9][10][11] However, there has been only one study that described UPROR following surgery for pediatric spinal deformity with every etiology, and even in that study, the follow-up period was limited to only 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies regarding mortality and morbidity after surgery for pediatric spinal deformities; however, there have been few that describe the incidence and risk factors for unplanned return to the operating room (UPROR). [1][2][3][4][5][6][7][8] Unplanned hospital readmissions and unplanned reoperation are a load on the health care system and can be an economic burden. Furthermore, UPROR is a useful quality indicator for surgical quality and risk management.…”
mentioning
confidence: 99%
“…Moreover, conservative treatment aims to avoid surgery (spinal fusion) that straightens the spine in the frontal plane and restores the sagittal and horizontal planes. Nevertheless, surgery has possible immediate side effects [ 10 , 11 ] and restricts spinal movement function with potential long-term consequences [ 12 ].…”
Section: Introductionmentioning
confidence: 99%